Editorial: The “theory of criminal procedure” and its relations between continents - Bruna Capparelli; Nereu José Giacomolli (Revista Brasileira de Direito Processual Penal)
In this editorial, the Authors expose the premises of consolidation points for a “theory of the criminal procedure” and its relations between Italian and Latin academics, laying down some guidelines that guide RBDPP.